Nanomedicines: Recent Progress, Impact and Challenges in Applications - Singh, Aditi (Asian Journal of Chemistry, 2021)
The ultra-fine size of nanoparticles gives them a unique material characteristics, such as remarkably vast surface area and high mobility or diffusibility in free state. They can be classified as hard or soft, depending upon the composition. Nanoparticles have proven to be highly promising in medicine, giving rise to a new field of study, nanomedicine. This rapidly evolving and upcoming branch of medicine is the study of nanomaterials and nanotechnology used for diagnosis, treatment and prevention of diseases. The review presented here summarizes the applications of nanotechnology in the field of medicine i.e. nanomedicine, specifically in diagnostics and drug delivery systems. It broadly covers nanotherapeutics with special focus on cancer, nanoformulations for drug delivery in biological systems, nanoimaging for diagnostics of life threatening diseases like cancer, CVD, neurodegenerative diseases and nanotoxicity on human health and concerns for environment safety.